Characterization of Anamnestic T-cell Responses Induced by Conventional Vaccines against Contagious Bovine Pleuropneumonia - Totte, Philippe; Yaya, Aboubakar; Sery, Amadou; Wesonga, Hezron; Wade, Abel; Naessens, Jan; Niang, Mamadou; Thiaucourt, François (Public Library of Science, 2013)
A better understanding of how T1 vaccination confers immunity would facilitate the rational design of improved vaccines against contagious bovine pleuropneumonia (CBPP). We show here that mycoplasmas-induced recall proliferation and IFN-γ responses are detected in cattle that received multiple shots of T1 vaccines. These anamnestic responses were under the strict control of CD4+ T lymphocytes. Moreover, CD62L expression indicated that both CD4+ effector memory (Tem) and central memory (Tcm) T lymphocytes are elicited in these animals. Comparative analysis with data from cattle that completely recovered from CBPP infection revealed similar anamnestic T-cell responses albeit at a lower magnitude for T1-vaccinated animals, particularly in the Tcm compartment. In conclusion, we discuss how our current understanding of T-cell responses will contribute to ongoing efforts for the improvement of future CBPP vaccines.